Supply Chain Management Information Systems Model for Educational Management for ASEAN University Network Quality Assurance at Institution Level - Artaphon Chansamu (International Journal of Supply Chain Management, 2022)
The purposes of  research to design and to evaluate supply chain management information systems model for educational management for ASEAN University Network Quality Assurance at institution level.The sample group in this study consisted of ten  experts consisted five experts on supply chain , three experts on information technology and two experts on curriculum. The research findings show that supply chain management information systems model for educational management for ASEAN University Network Quality Assurance at institution level comprises five main components, namely, main components,  suppliers , university  , customers and consumers. Evaluation results by the ten experts show the evaluation rating mean of 3.74 with standard deviation of 0.65  that supply chain management information systems model for educational management for ASEAN University Network Quality Assurance at institution level. is appropriate at the high level and can be appropriately applied in actual work settings.